Influência da presença de líquidos iônicos no comportamento térmico, termo-mecânico e nas propriedades de transporte em membranas de policarbonato obtidas via casting - Oliveira, Lucas Mendonça da Rocha (2014)
New alternatives to the use of polymeric membranes as solid electrolyte in fuel cells have been considered , in order to find solutions to recurrent obstacles that limit the performance of these cells, the dependence of the ionic transport due to the water content of the membrane and low thermal stability of the current polymers used . In this investigation, we sought an alternative, by studying the incorporation of imidazolium salts into polycarbonate (PC) matrix and the subsequent formation of membranes via casting. Characterizations that aimed to establish structure-property correlations by FTIR, DSC, TGA, DMTA, Water Vapor Permeation (WVT), Sorption and Desorption and Methanol Permeation were performed. The results indicated that the presence of different ionic liquids (IL) into the PC matrix significantly alter the structural and membrane transport characteristics analyzed.